Effect of thermal treatment on electrical conductivity of a polypyrrole film cast from the solution - Lee, J.Y.; Kim, D.Y.; Song, K.T.; Kim, S.Y.; Kim, C.Y. (SPE/ANTEC 1996 Proceedings, 1996)
A Polypyrrole(PPy) film cast from the solution should have intrinsic viscosity of higher than 0.094 dl/g in chloroform to exhibit excellent electrical conductivity close to 1 S/cm. The conductivity increases by one decade when a 100-μm thick film is heated to 250 °C in air. No change in the conductivity of a 100-μm thick film after the initial increase is observed during heating at up to 200 °C for 60 minutes. The conductivity drops on cooling the polymer to room temperature but shows higher than the original value except to be heated at 250 °C. However, a thinner film of 4 μm loses the conductivity during heating at 200 °C for 60 minutes and the surface resistivity increases with heating regardless of the film thickness. The decrease in the conductivity is caused by oxygen since no decrease is observed when heated in nitrogen. It is proposed that a carbonyl group is induced on the carbon at the position 3 in the pyrrole ring to break the conjugation in the polymer.